Fiber dressing for promoting wound healing and preparation method and application thereof

By using micro-nanofiber dressings with core-shell structure and combining with a variety of drugs, the irritation-free on-demand controllable adhesion and multi-stage immune regulation of diabetic wounds are achieved, and the problems of difficulty in wound healing and secondary damage in the prior art are solved, and the rapid healing and antibacterial effects of wounds are achieved.

CN119524185AActive Publication Date: 2025-02-28GENERAL HOSPITAL OF PLA

Patent Information

Application Number
CN202411755611.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-28
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The prior art is difficult to achieve irritation-free on-demand controllable adhesion and multi-stage immune regulation of diabetes wounds simultaneously, and conventional dressings are prone to destroying new epithelial tissues during dressing changes, resulting in secondary damage.

Method used

Micronanofibers with core-shell structures are used, and the shell contains hydrophilic and hydrophobic polymers, combining a variety of drugs such as curcumin, Centella asiaticin and silver nanoparticles to achieve non-stimulating adhesion and multi-stage drug release.

Benefits of technology

It achieves rapid healing of diabetic wounds, reduces the risk of secondary damage and infection, and has excellent biocompatibility and antibacterial properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005166934140000011
    Figure HDA0005166934140000011
  • Figure HDA0005166934140000012
    Figure HDA0005166934140000012
  • Figure HDA0005166934140000021
    Figure HDA0005166934140000021
Patent Text Reader

Abstract

The invention provides a fiber dressing for promoting wound healing and a preparation method and application thereof, and belongs to the technical field of biological materials. The shell of the fiber dressing contains the first medicine for promoting polarization of macrophages, and the first medicine can promote polarization of macrophages at normal and diabetic wound surfaces from M1 type to M2 type; a shell substrate is a mixture of hydrophilic and hydrophobic polymers, so that painless adhesion and stripping of a wound surface can be realized by absorbing seepage and spraying non-irritant normal saline on the wound surface, and secondary injury of the wound surface is reduced; an inner core contains a second medicine and a third medicine which are used for inducing death of M1 type macrophages, so that wound inflammatory response can be reduced, wound bacteria can be killed, wound infection degree can be reduced, and wound healing can be accelerated; the core matrix is a mixture of hydrophilic and hydrophobic polymers with good biocompatibility, can provide mechanical support for the fiber dressing, and provides a slow release effect for the two substances in the core. By controlling the composition of the inner core and the shell, the healing of normal wounds and diabetic wounds can be effectively promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomaterials, and in particular relates to a fiber dressing for promoting wound healing, a preparation method and an application thereof. Background Art

[0002] According to the International Diabetes Federation, as of 2021, approximately 537 million adults worldwide suffer from diabetes. Diabetic wounds are difficult to heal and have high disability and mortality rates, which not only cause great harm to the physical and mental health of patients, but also cause a large waste of medical resources. Long-term infection, secondary damage during dressing changes, and immune disorders at the wound surface may be the reasons that restrict its rapid healing. Therefore, inhibiting bacterial infection, achieving on-demand controllable adhesion, and regulating the immune response of the wound surface are factors that should be considered in designing ideal dressings.

[0003] At present, the dressings used in clinical care for diabetic wounds, such as hydrogels, foams, and semi-permeable membranes, usually adhere to the wound surface, destroy the new epithelial tissue during dressing changes, and cause secondary damage. On the other hand, most of these dressings are immunologically inert and cannot actively participate in immune regulation. Dressing design based on healing factors is a hot topic in the research of biomedical materials. Although there are some basic studies on on-demand controllable adhesion or immune regulation, there are the following problems: 1. The research on biomaterials that can simultaneously achieve on-demand controllable adhesion and multi-stage immune regulation is still in its infancy; 2. The stimuli in the on-demand controllable adhesion dressings developed based on stimulus-responsive strategies diffuse uncontrollably on the wound surface, stimulating the wound microenvironment; 3. Immunomodulatory dressings based on modified immunoactive macromolecules or loaded with stem cells, genes, drugs, etc. only focus on immune regulation at a single stage of healing. Therefore, it is urgent to develop an antibacterial dressing that can simultaneously achieve non-irritating on-demand controllable adhesion and multi-stage immune regulation functions in order to promote the rapid healing of diabetic wounds.

[0004] The prior art patent with the invention number CN115350316A discloses a hydrophilic fiber membrane whose inner core includes curcumin and a first spinnable polymer, and whose outer shell includes polyethylene glycol and a second spinnable polymer for realizing the slow release of curcumin. 1. The prior art focuses on preparing a hydrophilic fiber membrane that can realize the sustained release of curcumin. Its membrane can only release curcumin slowly, does not have controllable adhesion, hygroscopic dissolution, multi-stage release of two or more drugs, does not have antibacterial properties, and has not been tested in cells or animals to verify the feasibility of this material as a fiber dressing; the focus of the present invention is to realize non-irritating on-demand controllable adhesion, multi-stage immune regulation, and anti-wound infection at the same time. 2. The outer phase of the prior art cannot be dissolved, has only hydrophilic swelling properties, and does not have adhesion; the outer shell of the present invention is a mixture of water-soluble polymers and hydrophobic polymers. When encountering wound secretions, the water-soluble polymer can dissolve to achieve adhesion, and the hydrophobic polymer can avoid the sudden release of polarizing drugs. 3. The prior art can only achieve the sustained release of curcumin; however, the shell and the core of the present invention contain different drugs, thereby achieving multi-stage release of multiple drugs. Summary of the invention

[0005] The purpose of the present invention is to provide a fiber dressing having excellent wound healing promoting effects such as non-irritating on-demand controllable adhesion, multi-stage immune regulation, and resistance to wound infection, as well as a preparation method and application thereof.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a fiber dressing for promoting wound healing, which is composed of micro-nano fibers with a core-shell structure; the outer shell of the fiber comprises a first hydrophilic polymer, a first hydrophobic polymer and a first drug; the inner core of the fiber comprises a second hydrophilic polymer, a second hydrophobic polymer, a second drug and a third drug; the first drug comprises one or more of curcumin, naproxen, paeoniflorin, gallic acid, green tea extract, resveratrol, neurotensin, freeze-dried amniotic membrane-derived conditioned medium and miR-2235p mimics; the second drug comprises one or more of asiatica glycoside, quercetin, Fe3O4 nanoparticles, hemin, polyrotaxane containing methylated β-cyclodextrin, sorafenib, cyclosporin and Erastin; the third drug comprises one or more of silver nanoparticles, copper nanoparticles, antibacterial polypeptides and polyionic liquid antibacterial agents.

[0008] Preferably, the mass ratio of the first hydrophilic polymer, the first hydrophobic polymer and the first drug in the shell is (1-10):1:(0.1-0.5).

[0009] Preferably, the mass ratio of the second hydrophilic polymer, the second hydrophobic polymer, the second drug and the third drug in the inner core is 1:(1-10):(0.1-0.5):(0.1-0.2).

[0010] Preferably, the first hydrophilic polymer and the second hydrophilic polymer independently include one or more of polyvinyl pyrrolidone, gelatin, sodium alginate, carboxymethyl chitosan, polyvinyl alcohol, polyacrylic acid, recombinant spider silk protein, silk protein, polyethylene glycol, polyethylene oxide, tannic acid adhesive, dextran and pectin.

[0011] Preferably, the first hydrophobic polymer and the second hydrophobic polymer independently include one or more polymers selected from the group consisting of polycaprolactone, polyurethane, polylactic acid, polylactic acid-co-glycolic acid, cellulose acetate, polydimethylsiloxane, polymethacrylate, polyvinylidene fluoride, polyvinyl acetate, polyester, thermoplastic polyurethane elastomer, ethylene-vinyl acetate polymer, polyamide, polyimide and polylactic acid-co-glycolic acid and their derivatives.

[0012] The present invention also provides a method for preparing the fiber dressing for promoting wound healing described in the above technical solution, including a coaxial electrospinning method, a near-field direct writing method, a microfluidic spinning method or an immersion pulling method.

[0013] The present invention also provides the use of the fiber dressing for promoting wound healing described in the above technical solution or the fiber dressing for promoting wound healing prepared according to the preparation method described in the above technical solution in the preparation of wound dressings.

[0014] The present invention provides a fiber dressing for promoting wound healing, comprising micro-nano fibers with a core-shell structure; the outer shell of the fiber comprises a first hydrophilic polymer, a first hydrophobic polymer and a first drug; the inner core of the fiber comprises a second hydrophilic polymer, a second hydrophobic polymer, a second drug and a third drug; the first drug comprises one or more of curcumin, naproxen, paeoniflorin, gallic acid, green tea extract, resveratrol, neurotensin, freeze-dried amniotic membrane-derived conditioned medium and miR-2235p mimics; the second drug comprises one or more of asiatica glycoside, quercetin, Fe3O4 nanoparticles, hemin, polyrotaxane containing methylated β-cyclodextrin, sorafenib, cyclosporin and Erastin; the third drug comprises one or more of silver nanoparticles, copper nanoparticles, antibacterial polypeptides and polyionic liquid antibacterial agents. The fiber dressing provided by the present invention is composed of coaxial micro-nano fibers. The shell of the coaxial micro-nano fibers contains a first drug that promotes macrophage polarization, which can promote the polarization of macrophages in normal wounds and diabetic wounds from pro-inflammatory M1 type to anti-inflammatory M2 type; the shell contains a large amount of hydrophilic polymer, which absorbs exudate at the wound surface to achieve the "dissolution-infiltration-adhesion" effect and improve the adhesion strength. At the same time, its adhesion strength is mainly affected by the water content of the wound surface. By spraying non-irritating physiological saline, the fiber dressing can be effectively peeled off, reducing secondary damage to the wound surface, and adding a certain amount of The hydrophobic polymer can avoid the rapid burst release of the first drug and prolong the drug release time; the inner core contains a second drug that induces the death of M1 macrophages, which can reduce the number of M1 macrophages, reduce the inflammatory response of the wound, and accelerate wound healing; the inner core also contains a third drug that can effectively kill bacteria on the wound and reduce the degree of infection on the wound; the inner core has a large amount of hydrophobic polymer, and it still has a complete fiber structure after contacting water during use, which has a supporting effect, can effectively cover the wound, and is more conducive to the healing of the wound. Adding a certain amount of hydrophilic polymer makes the second drug have a suitable release rate. Controlling the composition of the fiber inner core and outer shell can effectively promote the healing of normal wounds and diabetic wounds. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The macroscopic image, microscopic top view and SEM image of a single broken coaxial micro-nano fiber of the fiber dressing in Example 3;

[0016] Figure 2 The cytotoxicity graphs of the control group (PBS), the fiber dressings in Example 3 and Comparative Examples 1 to 4, and 20% dimethyl sulfoxide (DMSO) on human umbilical vein endothelial cells (HUVECs);

[0017] Figure 3The cytotoxicity graphs of the control group (PBS), the fiber dressings in Example 3 and Comparative Examples 1 to 4, and 20% dimethyl sulfoxide (DMSO) on human fibroblasts (HDFs);

[0018] Figure 4 The cytotoxicity of the fiber dressings in Example 3 and Comparative Examples 1 to 4 to mouse macrophages;

[0019] Figure 5 This is a diagram showing the polarization of M1 macrophages promoted by the fiber dressings in Example 3 and Comparative Examples 1 to 4;

[0020] Figure 6 The diameters of the inhibition zones and the quantitative statistical graphs of the fiber dressings in Example 3 and Comparative Examples 1 to 4 against Staphylococcus aureus and Escherichia coli;

[0021] Figure 7 This is a graph showing the change in adhesion strength of the fiber dressing as a function of substrate moisture content in Example 3;

[0022] Figure 8 This is a diagram showing the controlled adhesion experiment of the fiber dressing in Example 3 on the mouse skin wound surface;

[0023] Fig. 9 The figure shows the healing promoting effect of the fiber dressings in Example 3 and Comparative Examples 1 to 4 on the wounds of diabetic mice infected with Staphylococcus aureus and the statistical graph of the wound healing area. DETAILED DESCRIPTION

[0024] The present invention provides a fiber dressing for promoting wound healing, comprising micro-nano fibers with a core-shell structure; the outer shell of the fiber comprises a first hydrophilic polymer, a first hydrophobic polymer and a first drug; the inner core of the fiber comprises a second hydrophilic polymer, a second hydrophobic polymer, a second drug and a third drug.

[0025] The fiber dressing provided by the present invention comprises micro-nano fibers with a core-shell structure.

[0026] In the present invention, the outer shell of the fiber includes a first hydrophilic polymer, a first hydrophobic polymer and a first drug.

[0027] In the present invention, the first hydrophilic polymer preferably includes one or more of polyvinyl pyrrolidone, gelatin, sodium alginate, carboxymethyl chitosan, polyvinyl alcohol, polyacrylic acid, recombinant spider silk protein, silk protein, polyethylene glycol, polyethylene oxide, tannic acid adhesive, dextran and pectin, more preferably polyvinyl pyrrolidone. In the present invention, the average molecular weight of the polyvinyl pyrrolidone is preferably 300000-400000Da, more preferably 360000Da. The present invention limits the average molecular weight of polyvinyl pyrrolidone within the above range, which can make the stability of the spinning solution better, and it has suitable solubility, has good adhesion after contact with the wound surface, and is also conducive to subsequent peeling from the wound surface, while allowing the first drug to have a suitable release rate.

[0028] In the present invention, the first hydrophobic polymer preferably includes one or more of the polymers in polycaprolactone, polyurethane, polylactic acid, polylactic acid-co-glycolic acid, cellulose acetate, polydimethylsiloxane, polymethacrylate, polyvinylidene fluoride, polyvinyl acetate, polyester, thermoplastic polyurethane elastomer, ethylene-vinyl acetate polymer, polyamide, polyimide and polylactic acid-co-glycolic acid and their derivatives, more preferably polycaprolactone. In the present invention, the average molecular weight of the polycaprolactone is preferably 10000-20000Da, more preferably 15000-20000Da. The present invention limits the average molecular weight of polycaprolactone within the above range, which can make the stability of the spinning solution better, more conducive to the preparation of fiber dressings, and can also avoid the sudden release of drugs in the shell, which is more conducive to the healing of the wound surface.

[0029] In the present invention, the first drug includes one or more of curcumin, naproxen, paeoniflorin, gallic acid, green tea extract, resveratrol, neurotensin, freeze-dried amniotic membrane-derived conditioned medium and miR-2235p mimics, preferably curcumin. In the present invention, the first drug can promote macrophage polarization, promote macrophages on normal wounds and diabetic wounds to polarize from pro-inflammatory M1 type to anti-inflammatory M2 type, and polarized M2 type macrophages can secrete a variety of cytokines and growth factors, promote angiogenesis, collagen deposition and granulation, promote diabetic wounds from the inflammatory phase to the proliferation phase, and accelerate wound healing.

[0030] In the present invention, the mass ratio of the first hydrophilic polymer, the first hydrophobic polymer and the first drug in the shell is preferably (1-10):1:(0.1-0.5), more preferably (2-10):1:(0.1-0.5), and further preferably (5-10):1:(0.1-0.5). The present invention limits the mass ratio of the first hydrophilic polymer, the first hydrophobic polymer and the first drug in the shell to the above range. The shell contains more hydrophilic polymers, which absorb exudate at the wound surface to achieve the "dissolution-infiltration-adhesion" effect and improve the adhesion strength. At the same time, its adhesion strength is mainly affected by the water content of the wound surface. By spraying non-irritating physiological saline, the fiber dressing can be effectively peeled off, reducing secondary damage to the wound surface. Adding a certain amount of hydrophobic polymer can avoid the rapid burst release of the first drug and prolong the drug release time.

[0031] In the present invention, the inner core of the fiber includes a second hydrophilic polymer, a second hydrophobic polymer, a second drug and a third drug.

[0032] In the present invention, the second hydrophilic polymer preferably includes one or more of polyvinyl pyrrolidone, gelatin, sodium alginate, carboxymethyl chitosan, polyvinyl alcohol, polyacrylic acid, recombinant spider silk protein, silk protein, polyethylene glycol, polyethylene oxide, tannic acid adhesive, dextran and pectin, more preferably polyvinyl pyrrolidone. In the present invention, the average molecular weight of the polyvinyl pyrrolidone is preferably 300000-400000Da, more preferably 360000Da. The present invention limits the average molecular weight of polyvinyl pyrrolidone to the above range, and it has suitable solubility, so that the drug in the inner core has a suitable release rate.

[0033] In the present invention, the second hydrophobic polymer preferably includes one or more of the polymers in polycaprolactone, polyurethane, polylactic acid, polylactic acid-co-glycolic acid, cellulose acetate, polydimethylsiloxane, polymethacrylate, polyvinylidene fluoride, polyvinyl acetate, polyester, thermoplastic polyurethane elastomer, ethylene-vinyl acetate polymer, polyamide, polyimide and polylactic acid-co-glycolic acid and their derivatives, more preferably polycaprolactone. In the present invention, the average molecular weight of the polycaprolactone is preferably 10000-20000Da, more preferably 15000-20000Da. The present invention limits the average molecular weight of polycaprolactone within the above range, so that it can maintain the structure of the fiber membrane during use, effectively cover the wound, and be more conducive to wound healing.

[0034] In the present invention, the second drug includes one or more of asiatica glycoside, quercetin, Fe3O4 nanoparticles, hemin, polyrotaxane containing methylated β-cyclodextrin, sorafenib, cyclosporine and Erastin, preferably asiatica glycoside. In the present invention, the second drug can induce M1 macrophage cell death, reduce the number of M1 macrophages, reduce wound inflammatory response, and accelerate wound healing.

[0035] In the present invention, the third drug preferably includes one or more of silver nanoparticles, copper nanoparticles, antimicrobial polypeptides and polyionic liquid antimicrobial agents, and more preferably silver nanoparticles. In the present invention, the third drug can kill gram-positive bacteria (such as Staphylococcus aureus) and gram-negative bacteria (such as Escherichia coli) on the wound surface, reduce the degree of infection on the wound surface, and promote wound healing.

[0036] In the present invention, the mass ratio of the second hydrophilic polymer, the second hydrophobic polymer, the second drug and the third drug in the inner core is preferably 1: (1-10): (0.1-0.5): (0.1-0.2), more preferably 1: (3-10): (0.1-0.5): (0.1-0.2), and further preferably 1: (5-10): (0.1-0.5): (0.1-0.2). The present invention limits the mass ratio of the second hydrophilic polymer, the second hydrophobic polymer, the second drug and the third drug in the inner core to the above range. The inner core has more hydrophobic polymers, and still has a complete fiber structure after contacting water during use, has a supporting effect, can effectively cover the wound surface, and is more conducive to the healing of the wound surface. A certain amount of hydrophilic polymer is added to make the second drug have a suitable release rate.

[0037] The fiber dressing of the present invention is composed of micro-nano fibers with a core-shell structure. The outer shell of the fiber contains a first drug that promotes macrophage polarization, which can promote the polarization of macrophages on normal wounds and diabetic wounds from pro-inflammatory M1 type to anti-inflammatory M2 type; the matrix of the outer shell is a mixture of hydrophilic polymers and hydrophobic polymers, which can absorb exudate at the wound surface to achieve the "dissolution-infiltration-adhesion" effect, and the fiber membrane can be effectively peeled off by spraying non-irritating physiological saline, achieving controllable wet adhesion and reducing secondary damage to the wound surface; the inner core contains a second drug that induces the death of M1 macrophages, which can reduce the number of M1 macrophages, reduce the inflammatory response of the wound surface, and accelerate the healing of the wound surface. Healing; the inner core also contains a third drug, which can effectively kill bacteria on the wound and reduce the degree of infection on the wound; the matrix of the inner core is a mixture of hydrophilic polymers and hydrophobic polymers with good biocompatibility, which can provide mechanical support for the fiber dressing and provide a sustained-release effect for the two substances in the inner core; controlling the types and proportions of hydrophilic polymers, hydrophobic polymers and drugs in the outer shell and the inner core can adjust the release rate of the drug and further promote wound healing. At the same time, the fiber dressing has excellent biocompatibility, non-irritation and the ability to promote the proliferation of endothelial cells and fibroblasts, and can achieve non-irritation, on-demand controllable adhesion on the wound, with the characteristics of non-irritation adhesion and easy peeling, and controlled drug release rate.

[0038] The present invention also provides a method for preparing the fiber dressing for promoting wound healing as described in the above technical solution, including coaxial electrospinning, near-field direct writing, microfluidic spinning or immersion pulling, preferably coaxial electrospinning.

[0039] In the present invention, the coaxial electrospinning method preferably comprises the following steps:

[0040] (1) mixing a first hydrophilic polymer, a first hydrophobic polymer, a first drug and a first solvent to obtain a shell spinning solution;

[0041] (2) mixing a second hydrophilic polymer, a second hydrophobic polymer, a second drug, a third drug and a second solvent to obtain a core spinning solution;

[0042] (3) coaxially electrospinning the shell spinning solution obtained in step (1) and the core spinning solution obtained in step (2) to obtain a fiber dressing that promotes wound healing;

[0043] There is no chronological order for steps (1) and (2).

[0044] Unless otherwise specified, the present invention has no particular limitation on the sources of the raw materials, and commercially available products known to those skilled in the art may be used.

[0045] In the present invention, the first hydrophilic polymer, the first hydrophobic polymer, the first drug and the first solvent are preferably mixed to obtain the shell spinning solution.

[0046] In the present invention, the first solvent preferably includes dimethylformamide (DMF) and anhydrous ethanol; the mass ratio of DMF to anhydrous ethanol is preferably (8-10): 1, more preferably 9: 1. The present invention limits the composition and ratio of the first solvent to the above range, which can improve the spinnability of electrospinning.

[0047] In the present invention, the mass concentration of the first hydrophilic polymer in the shell spinning solution is preferably 1.5-15%. The present invention limits the mass concentration of the first hydrophilic polymer in the shell spinning solution to the above range, which can make it fully dissolved and is more conducive to electrospinning.

[0048] In the present invention, the mass ratio of the first hydrophilic polymer, the first hydrophobic polymer and the first drug in the shell spinning solution is preferably (1-10):1:(0.1-0.5), more preferably (3-10):1:(0.1-0.5), and further preferably (5-10):1:(0.1-0.5). The present invention can control the adhesion strength of the fiber dressing shell and the release rate of the first drug by controlling the mass ratio of the first hydrophilic polymer, the first hydrophobic polymer and the first drug in the shell spinning solution, so that the fiber dressing can be more conducive to the healing of the wound surface.

[0049] The present invention has no special limitation on the mixing operation of the first hydrophilic polymer, the first hydrophobic polymer, the first drug and the first solvent. The raw materials can be uniformly mixed using a mixing technical solution well known to those skilled in the art.

[0050] In the present invention, the second hydrophilic polymer, the second hydrophobic polymer, the second drug, the third drug and the second solvent are preferably mixed to obtain the core spinning solution.

[0051] In the present invention, when the third drug is silver nanoparticles, the present invention preferably adds a metal salt of the third drug, that is, a silver salt. In the present invention, the silver salt is preferably silver nitrate.

[0052] In the present invention, when the third drug is copper nanoparticles, the present invention preferably adds a metal salt of the third drug, that is, a copper salt. In the present invention, the copper salt is preferably copper nitrate.

[0053] In the present invention, the second solvent preferably includes DMF and tetrahydrofuran; the mass ratio of DMF to tetrahydrofuran is preferably (1-2): 1, more preferably (1-1.5): 1. The present invention limits the composition and ratio of the second solvent to the above range, which can improve the spinnability of electrospinning.

[0054] In the present invention, the mass concentration of the second hydrophilic polymer in the core spinning solution is preferably 1.5-7.5%. The present invention limits the mass concentration of the second hydrophilic polymer in the core spinning solution to the above range, which can ensure the mechanical strength of the core while regulating the release rate of the second drug and the third drug.

[0055] In the present invention, when the third drug is directly added, the mass ratio of the second hydrophilic polymer, the second hydrophobic polymer, the second drug and the third drug in the core spinning solution is preferably 1: (1-10): (0.1-0.5): (0.1-0.2).

[0056] In the present invention, when the metal salt of the third drug is added, the mass ratio of the second hydrophilic polymer, the second hydrophobic polymer, the second drug and the metal salt of the third drug in the inner core spinning solution is preferably 1: (1-10): (0.1-0.5): (0.1-0.3). The present invention limits the mass ratio of the second hydrophilic polymer, the second hydrophobic polymer, the second drug and the third drug or the metal salt of the third drug in the inner core spinning solution to the above range, and can regulate the release rate of the second drug and the third drug while ensuring the mechanical strength of the inner core, thereby obtaining better anti-wound infection and anti-inflammatory effects, so that the fiber dressing can be more conducive to wound healing.

[0057] After obtaining the outer shell spinning solution and the inner core spinning solution, the present invention preferably performs coaxial electrospinning on the outer shell spinning solution and the inner core spinning solution to obtain a fiber dressing that promotes wound healing.

[0058] In the present invention, the ambient temperature during the coaxial electrospinning is preferably 30-40°C; the ambient humidity during the coaxial electrospinning is preferably 20-40RH%. The present invention limits the ambient temperature and humidity to the above ranges, which can make the solvent in the spinning solution evaporate quickly and avoid adhesion between fibers.

[0059] In the present invention, during the coaxial electrospinning, the flow rate of the outer shell spinning solution is preferably 0.6-1.5 mL / h, more preferably 0.8-1.2 mL / h; during the coaxial electrospinning, the flow rate of the inner core spinning solution is preferably 0.2-1.2 mL / h, more preferably 0.4-1.0 mL / h; during the coaxial electrospinning, the flow rate ratio of the outer shell spinning solution to the inner core spinning solution is preferably (1-6): 1. The present invention can adjust the thickness ratio of the outer shell and the inner core in the fiber dressing by adjusting the flow rate ratio of the outer shell spinning solution to the inner core spinning solution during coaxial electrospinning.

[0060] In the present invention, the voltage of the coaxial electrospinning is preferably 15-20 kV, more preferably 18 kV; the receiving distance of the coaxial electrospinning is preferably 20-25 cm, more preferably 21 cm; the time of the coaxial electrospinning is 1-5 h, more preferably 2-4 h. In the present invention, during the coaxial electrospinning, the silver salt or copper salt is reduced by DMF to silver nanoparticles or copper nanoparticles as the third drug. The present invention limits the parameters of the coaxial electrospinning within the above range, which can be more conducive to obtaining fibers with uniform thickness and regular morphology.

[0061] In the present invention, a hydrophobic spray is preferably sprayed on the receiving device before the coaxial electrospinning. The present invention has no special restrictions on the type and spraying amount of the hydrophobic spray, as long as it can ensure that the fiber is smoothly peeled off from the surface of the receiving device. In the present invention, the hydrophobic spray is preferably a super-hydrophobic silica nanoparticle spray.

[0062] After the coaxial electrospinning is completed, the present invention preferably dries the coaxial electrospinning product to obtain a fiber dressing that promotes wound healing.

[0063] In the present invention, the drying temperature is preferably 30 to 50° C., more preferably 40° C.; the drying time is preferably 12 to 36 hours, more preferably 24 hours.

[0064] The present invention has no special limitation on the specific operation of the near-field direct writing method, microfluidic spinning method or immersion pulling method, and the technical solutions well known to those skilled in the art can be adopted.

[0065] The present invention also provides the use of the fiber dressing for promoting wound healing described in the above technical solution or the fiber dressing for promoting wound healing prepared according to the preparation method described in the above technical solution in the preparation of wound dressings.

[0066] In the present invention, the wound surface is preferably a diabetic wound surface.

[0067] The fiber dressing provided by the present invention has excellent biocompatibility, antibacterial property, no irritation, and controllable adhesion, so that the prepared wound dressing has excellent wound healing promoting effect.

[0068] The present invention has no special limitation on the operation of using the fiber dressing in preparing wound dressings, and the application technical solutions well known to those skilled in the art can be adopted.

[0069] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0070] The polyvinyl pyrrolidone and polycaprolactone used in each example were purchased from Sigma-Aldrich, and DMF, anhydrous ethanol and tetrahydrofuran were purchased from Aladdin Biological Reagent Company.

[0071] Example 1

[0072] A fiber dressing for promoting wound healing, comprising micro-nano fibers with a core-shell structure, wherein the outer shell of the fiber is composed of polyvinyl pyrrolidone (average molecular weight 360,000 Da), polycaprolactone (average molecular weight 18,000 Da) and curcumin; the inner core of the fiber is composed of polyvinyl pyrrolidone (average molecular weight 360,000 Da), polycaprolactone (average molecular weight 18,000 Da), asiaticoside and silver nanoparticles; the mass ratio of polyvinyl pyrrolidone, polycaprolactone and curcumin in the outer shell is 9:1:0.3; the mass ratio of polyvinyl pyrrolidone, polycaprolactone, asiaticoside and silver nanoparticles in the inner core is 1:9:0.33:0.13;

[0073] The preparation method of the fiber dressing is as follows:

[0074] (1) mixing polyvinyl pyrrolidone, polycaprolactone, curcumin, DMF and anhydrous ethanol to obtain a shell spinning solution, wherein the mass concentration of polyvinyl pyrrolidone is 15%, the mass concentration of polycaprolactone is 1.7%, the mass concentration of curcumin is 0.5%, the mass ratio of DMF to anhydrous ethanol is 9:1, and the mass ratio of polyvinyl pyrrolidone, polycaprolactone and curcumin in the shell spinning solution is 9:1:0.3;

[0075] (2) mixing polyvinyl pyrrolidone, polycaprolactone, asiaticoside, silver nitrate, DMF and tetrahydrofuran to obtain a core spinning solution, wherein the mass concentration of polyvinyl pyrrolidone is 1.5%, the mass concentration of polycaprolactone is 13.4%, the mass concentration of asiaticoside is 0.5%, the mass concentration of silver nitrate is 0.3%, the mass ratio of DMF to tetrahydrofuran is 1.05:1, and the mass ratio of polyvinyl pyrrolidone, polycaprolactone, asiaticoside and silver nitrate in the core spinning solution is 1:9:0.33:0.2;

[0076] (3) The ambient temperature was controlled at 35°C, and the ambient humidity was controlled at 25RH%. A hydrophobic spray was sprayed on the receiving device of the electrospinning machine. The coaxial electrospinning pillow was placed 21 cm away from the receiving end. The flow rate of the outer shell spinning solution was 1.2 mL / h, and the flow rate of the inner core spinning solution was 1.0 mL / h (the flow rate ratio of the outer shell spinning solution to the inner core spinning solution was 1.2:1). The voltage was increased to 18 kV to form a Taylor cone at the needle tip. The electrospinning was performed for 3 hours. The fiber membrane was removed from the receiving end and dried in an oven at 45°C for 24 hours to obtain a fiber dressing.

[0077] Example 2

[0078] The flow rate of the inner core spinning solution in step (3) of Example 1 was replaced with 0.8 mL / h. At this time, the flow rate ratio of the outer shell spinning solution to the inner core spinning solution was 1.5:1. Other parameters were the same as those in Example 1, and a fiber dressing was obtained.

[0079] Example 3

[0080] The flow rate of the inner core spinning solution in step (3) of Example 1 was replaced with 0.6 mL / h. At this time, the flow rate ratio of the outer shell spinning solution to the inner core spinning solution was 2:1. The other parameters were the same as those in Example 1, and a fiber dressing was obtained, which was recorded as CUR / AS+Ag-loaded.

[0081] Example 4

[0082] The flow rate of the inner core spinning solution in step (3) of Example 1 was replaced with 0.4 mL / h. At this time, the flow rate ratio of the outer shell spinning solution to the inner core spinning solution was 3:1. Other parameters were the same as those in Example 1, and a fiber dressing was obtained.

[0083] Example 5

[0084] The flow rate of the inner core spinning solution in step (3) of Example 1 was replaced with 0.2 mL / h. At this time, the flow rate ratio of the outer shell spinning solution to the inner core spinning solution was 6:1. Other parameters were the same as those in Example 1, and a fiber dressing was obtained.

[0085] Example 6

[0086] A fiber dressing for promoting wound healing, comprising micro-nano fibers with a core-shell structure, wherein the outer shell of the fiber is composed of polyvinyl pyrrolidone (average molecular weight 360,000 Da), polycaprolactone (average molecular weight 18,000 Da) and curcumin; the inner core of the fiber is composed of polyvinyl pyrrolidone (average molecular weight 360,000 Da), polycaprolactone (average molecular weight 18,000 Da), asiaticoside and silver nanoparticles; the mass ratio of polyvinyl pyrrolidone, polycaprolactone and curcumin in the outer shell is 8:1:0.3; the mass ratio of polyvinyl pyrrolidone, polycaprolactone, asiaticoside and silver nanoparticles in the inner core is 1:9:0.33:0.13;

[0087] The preparation method of the fiber dressing is as follows:

[0088] (1) mixing polyvinyl pyrrolidone, polycaprolactone, curcumin, DMF and anhydrous ethanol to obtain a shell spinning solution, wherein the mass concentration of polyvinyl pyrrolidone is 13.6%, the mass concentration of polycaprolactone is 1.7%, the mass concentration of curcumin is 0.5%, the mass ratio of DMF to anhydrous ethanol is 9:1, and the mass ratio of polyvinyl pyrrolidone, polycaprolactone and curcumin in the shell spinning solution is 8:1:0.3;

[0089] (2) mixing polyvinyl pyrrolidone, polycaprolactone, asiaticoside, silver nitrate, DMF and tetrahydrofuran to obtain a core spinning solution, wherein the mass concentration of polyvinyl pyrrolidone is 1.5%, the mass concentration of polycaprolactone is 13.4%, the mass concentration of asiaticoside is 0.5%, the mass concentration of silver nitrate is 0.3%, the mass ratio of DMF to tetrahydrofuran is 1.05:1, and the mass ratio of polyvinyl pyrrolidone, polycaprolactone, asiaticoside and silver nitrate in the core spinning solution is 1:9:0.33:0.2;

[0090] (3) The ambient temperature was controlled at 35°C, and the ambient humidity was controlled at 25RH%. A hydrophobic spray was sprayed on the receiving device of the electrospinning machine. The coaxial electrospinning pillow was placed 21 cm away from the receiving end. The flow rate of the outer shell spinning solution was 1.2 mL / h, and the flow rate of the inner core spinning solution was 0.6 mL / h (the flow rate ratio of the outer shell spinning solution to the inner core spinning solution was 2:1). The voltage was increased by 18 kV to form a Taylor cone at the needle tip. The electrospinning was performed for 3 hours. The fiber membrane was removed from the receiving end and dried in an oven at 45°C for 24 hours to obtain a fiber dressing.

[0091] Example 7

[0092] A fiber dressing for promoting wound healing, comprising micro-nano fibers with a core-shell structure, wherein the outer shell of the fiber is composed of polyvinyl pyrrolidone (average molecular weight 360,000 Da), polycaprolactone (average molecular weight 18,000 Da) and curcumin; the inner core of the fiber is composed of polyvinyl pyrrolidone (average molecular weight 360,000 Da), polycaprolactone (average molecular weight 18,000 Da), asiaticoside and silver nanoparticles; the mass ratio of polyvinyl pyrrolidone, polycaprolactone and curcumin in the outer shell is 4:1:0.3; the mass ratio of polyvinyl pyrrolidone, polycaprolactone, asiaticoside and silver nanoparticles in the inner core is 1:9:0.33:0.13;

[0093] The preparation method of the fiber dressing is as follows:

[0094] (1) mixing polyvinyl pyrrolidone, polycaprolactone, curcumin, DMF and anhydrous ethanol to obtain a shell spinning solution, wherein the mass concentration of polyvinyl pyrrolidone is 6.8%, the mass concentration of polycaprolactone is 1.7%, the mass concentration of curcumin is 0.5%, the mass ratio of DMF to anhydrous ethanol is 9:1, and the mass ratio of polyvinyl pyrrolidone, polycaprolactone and curcumin in the shell spinning solution is 4:1:0.3;

[0095] (2)~(3) are the same as Example 6.

[0096] Example 8

[0097] A fiber dressing for promoting wound healing, comprising micro-nano fibers with a core-shell structure, wherein the outer shell of the fiber is composed of polyvinyl pyrrolidone (average molecular weight 360,000 Da), polycaprolactone (average molecular weight 18,000 Da) and curcumin; the inner core of the fiber is composed of polyvinyl pyrrolidone (average molecular weight 360,000 Da), polycaprolactone (average molecular weight 18,000 Da), asiaticoside and silver nanoparticles; the mass ratio of polyvinyl pyrrolidone, polycaprolactone and curcumin in the outer shell is 2:1:0.3; the mass ratio of polyvinyl pyrrolidone, polycaprolactone, asiaticoside and silver nanoparticles in the inner core is 1:9:0.33:0.13;

[0098] The preparation method of the fiber dressing is as follows:

[0099] (1) mixing polyvinyl pyrrolidone, polycaprolactone, curcumin, DMF and anhydrous ethanol to obtain a shell spinning solution, wherein the mass concentration of polyvinyl pyrrolidone is 3.4%, the mass concentration of polycaprolactone is 1.7%, the mass concentration of curcumin is 0.5%, the mass ratio of DMF to anhydrous ethanol is 9:1, and the mass ratio of polyvinyl pyrrolidone, polycaprolactone and curcumin in the shell spinning solution is 2:1:0.3;

[0100] (2)~(3) are the same as Example 6.

[0101] Example 9

[0102] A fiber dressing for promoting wound healing, comprising micro-nano fibers with a core-shell structure, wherein the outer shell of the fiber is composed of polyvinyl pyrrolidone (average molecular weight 360,000 Da), polycaprolactone (average molecular weight 18,000 Da) and curcumin; the inner core of the fiber is composed of polyvinyl pyrrolidone (average molecular weight 360,000 Da), polycaprolactone (average molecular weight 18,000 Da), asiaticoside and silver nanoparticles; the mass ratio of polyvinyl pyrrolidone, polycaprolactone and curcumin in the outer shell is 1.5:1:0.3; the mass ratio of polyvinyl pyrrolidone, polycaprolactone, asiaticoside and silver nanoparticles in the inner core is 1:9:0.33:0.13;

[0103] The preparation method of the fiber dressing is as follows:

[0104] (1) mixing polyvinyl pyrrolidone, polycaprolactone, curcumin, DMF and anhydrous ethanol to obtain a shell spinning solution, wherein the mass concentration of polyvinyl pyrrolidone is 2.55%, the mass concentration of polycaprolactone is 1.7%, the mass concentration of curcumin is 0.5%, the mass ratio of DMF to anhydrous ethanol is 9:1, and the mass ratio of polyvinyl pyrrolidone, polycaprolactone and curcumin in the shell spinning solution is 1.5:1:0.3;

[0105] (2)~(3) are the same as Example 6.

[0106] Example 10

[0107] A fiber dressing for promoting wound healing, comprising micro-nano fibers with a core-shell structure, wherein the outer shell of the fiber is composed of polyvinyl pyrrolidone (average molecular weight 360,000 Da), polycaprolactone (average molecular weight 18,000 Da) and curcumin; the inner core of the fiber is composed of polyvinyl pyrrolidone (average molecular weight 360,000 Da), polycaprolactone (average molecular weight 18,000 Da), asiaticoside and silver nanoparticles; the mass ratio of polyvinyl pyrrolidone, polycaprolactone and curcumin in the outer shell is 1:1:0.3; the mass ratio of polyvinyl pyrrolidone, polycaprolactone, asiaticoside and silver nanoparticles in the inner core is 1:9:0.33:0.13;

[0108] The preparation method of the fiber dressing is as follows:

[0109] (1) mixing polyvinyl pyrrolidone, polycaprolactone, curcumin, DMF and anhydrous ethanol to obtain a shell spinning solution, wherein the mass concentration of polyvinyl pyrrolidone is 1.7%, the mass concentration of polycaprolactone is 1.7%, the mass concentration of curcumin is 0.5%, the mass ratio of DMF to anhydrous ethanol is 9:1, and the mass ratio of polyvinyl pyrrolidone, polycaprolactone and curcumin in the shell spinning solution is 1:1:0.3;

[0110] (2)~(3) are the same as Example 6.

[0111] Embodiment 11

[0112] A fiber dressing for promoting wound healing, comprising micro-nano fibers with a core-shell structure, wherein the outer shell of the fiber is composed of polyvinyl pyrrolidone (average molecular weight 360,000 Da), polycaprolactone (average molecular weight 18,000 Da) and curcumin; the inner core of the fiber is composed of polyvinyl pyrrolidone (average molecular weight 360,000 Da), polycaprolactone (average molecular weight 18,000 Da), asiaticoside and silver nanoparticles; the mass ratio of polyvinyl pyrrolidone, polycaprolactone and curcumin in the outer shell is 1:1:0.3; the mass ratio of polyvinyl pyrrolidone, polycaprolactone, asiaticoside and silver nanoparticles in the inner core is 1:8:0.33:0.13;

[0113] The preparation method of the fiber dressing is as follows:

[0114] (1) mixing polyvinyl pyrrolidone, polycaprolactone, curcumin, DMF and anhydrous ethanol to obtain a shell spinning solution, wherein the mass concentration of polyvinyl pyrrolidone is 1.7%, the mass concentration of polycaprolactone is 1.7%, the mass concentration of curcumin is 0.5%, the mass ratio of DMF to anhydrous ethanol is 9:1, and the mass ratio of polyvinyl pyrrolidone, polycaprolactone and curcumin in the shell spinning solution is 1:1:0.3;

[0115] (2) mixing polyvinyl pyrrolidone, polycaprolactone, asiaticoside, silver nitrate, DMF and tetrahydrofuran to obtain a core spinning solution, wherein the mass concentration of polyvinyl pyrrolidone is 1.5%, the mass concentration of polycaprolactone is 12%, the mass concentration of asiaticoside is 0.5%, the mass concentration of silver nitrate is 0.3%, the mass ratio of DMF to tetrahydrofuran is 1.05:1, and the mass ratio of polyvinyl pyrrolidone, polycaprolactone, asiaticoside and silver nitrate in the core spinning solution is 1:8:0.33:0.2;

[0116] (3) The ambient temperature was controlled at 35°C, and the ambient humidity was controlled at 25RH%. A hydrophobic spray was sprayed on the receiving device of the electrospinning machine. The coaxial electrospinning pillow was placed 21 cm away from the receiving end. The flow rate of the outer shell spinning solution was 1.2 mL / h, and the flow rate of the inner core spinning solution was 0.6 mL / h (the flow rate ratio of the outer shell spinning solution to the inner core spinning solution was 2:1). The voltage was increased by 18 kV to form a Taylor cone at the needle tip. The electrospinning was performed for 3 hours. The fiber membrane was removed from the receiving end and dried in an oven at 45°C for 24 hours to obtain a fiber dressing.

[0117] Example 12

[0118] A fiber dressing for promoting wound healing, comprising micro-nano fibers with a core-shell structure, wherein the outer shell of the fiber is composed of polyvinyl pyrrolidone (average molecular weight 360,000 Da), polycaprolactone (average molecular weight 18,000 Da) and curcumin; the inner core of the fiber is composed of polyvinyl pyrrolidone (average molecular weight 360,000 Da), polycaprolactone (average molecular weight 18,000 Da), asiaticoside and silver nanoparticles; the mass ratio of polyvinyl pyrrolidone, polycaprolactone and curcumin in the outer shell is 1:1:0.3; the mass ratio of polyvinyl pyrrolidone, polycaprolactone, asiaticoside and silver nanoparticles in the inner core is 1:4:0.33:0.13;

[0119] The preparation method of the fiber dressing is as follows:

[0120] (1) mixing polyvinyl pyrrolidone, polycaprolactone, curcumin, DMF and anhydrous ethanol to obtain a shell spinning solution, wherein the mass concentration of polyvinyl pyrrolidone is 1.7%, the mass concentration of polycaprolactone is 1.7%, the mass concentration of curcumin is 0.5%, the mass ratio of DMF to anhydrous ethanol is 9:1, and the mass ratio of polyvinyl pyrrolidone, polycaprolactone and curcumin in the shell spinning solution is 1:1:0.3;

[0121] (2) mixing polyvinyl pyrrolidone, polycaprolactone, asiaticoside, silver nitrate, DMF and tetrahydrofuran to obtain a core spinning solution, wherein the mass concentration of polyvinyl pyrrolidone is 1.5%, the mass concentration of polycaprolactone is 6%, the mass concentration of asiaticoside is 0.5%, the mass concentration of silver nitrate is 0.3%, the mass ratio of DMF to tetrahydrofuran is 1.05:1, and the mass ratio of polyvinyl pyrrolidone, polycaprolactone, asiaticoside and silver nitrate in the core spinning solution is 1:4:0.33:0.2;

[0122] (3) The ambient temperature was controlled at 35°C, and the ambient humidity was controlled at 25RH%. A hydrophobic spray was sprayed on the receiving device of the electrospinning machine. The coaxial electrospinning pillow was placed 21 cm away from the receiving end. The flow rate of the outer shell spinning solution was 1.2 mL / h, and the flow rate of the inner core spinning solution was 0.6 mL / h (the flow rate ratio of the outer shell spinning solution to the inner core spinning solution was 2:1). The voltage was increased by 18 kV to form a Taylor cone at the needle tip. The electrospinning was performed for 3 hours. The fiber membrane was removed from the receiving end and dried in an oven at 45°C for 24 hours to obtain a fiber dressing.

[0123] Example 13

[0124] A fiber dressing for promoting wound healing, comprising micro-nano fibers with a core-shell structure, wherein the outer shell of the fiber is composed of polyvinyl pyrrolidone (average molecular weight 360,000 Da), polycaprolactone (average molecular weight 18,000 Da) and curcumin; the inner core of the fiber is composed of polyvinyl pyrrolidone (average molecular weight 360,000 Da), polycaprolactone (average molecular weight 18,000 Da), asiaticoside and silver nanoparticles; the mass ratio of polyvinyl pyrrolidone, polycaprolactone and curcumin in the outer shell is 1:1:0.3; the mass ratio of polyvinyl pyrrolidone, polycaprolactone, asiaticoside and silver nanoparticles in the inner core is 1:2:0.33:0.13;

[0125] The preparation method of the fiber dressing is as follows:

[0126] (1) mixing polyvinyl pyrrolidone, polycaprolactone, curcumin, DMF and anhydrous ethanol to obtain a shell spinning solution, wherein the mass concentration of polyvinyl pyrrolidone is 1.7%, the mass concentration of polycaprolactone is 1.7%, the mass concentration of curcumin is 0.5%, the mass ratio of DMF to anhydrous ethanol is 9:1, and the mass ratio of polyvinyl pyrrolidone, polycaprolactone and curcumin in the shell spinning solution is 1:1:0.3;

[0127] (2) mixing polyvinyl pyrrolidone, polycaprolactone, asiaticoside, silver nitrate, DMF and tetrahydrofuran to obtain a core spinning solution, wherein the mass concentration of polyvinyl pyrrolidone is 1.5%, the mass concentration of polycaprolactone is 3%, the mass concentration of asiaticoside is 0.5%, the mass concentration of silver nitrate is 0.3%, the mass ratio of DMF to tetrahydrofuran is 1.05:1, and the mass ratio of polyvinyl pyrrolidone, polycaprolactone, asiaticoside and silver nitrate in the core spinning solution is 1:2:0.33:0.2;

[0128] (3) The ambient temperature was controlled at 35°C, and the ambient humidity was controlled at 25RH%. A hydrophobic spray was sprayed on the receiving device of the electrospinning machine. The coaxial electrospinning pillow was placed 21 cm away from the receiving end. The flow rate of the outer shell spinning solution was 1.2 mL / h, and the flow rate of the inner core spinning solution was 0.6 mL / h (the flow rate ratio of the outer shell spinning solution to the inner core spinning solution was 2:1). The voltage was increased by 18 kV to form a Taylor cone at the needle tip. The electrospinning was performed for 3 hours. The fiber membrane was removed from the receiving end and dried in an oven at 45°C for 24 hours to obtain a fiber dressing.

[0129] Embodiment 14

[0130] A fiber dressing for promoting wound healing, comprising micro-nano fibers with a core-shell structure, wherein the outer shell of the fiber is composed of polyvinyl pyrrolidone (average molecular weight 360,000 Da), polycaprolactone (average molecular weight 18,000 Da) and curcumin; the inner core of the fiber is composed of polyvinyl pyrrolidone (average molecular weight 360,000 Da), polycaprolactone (average molecular weight 18,000 Da), asiaticoside and silver nanoparticles; the mass ratio of polyvinyl pyrrolidone, polycaprolactone and curcumin in the outer shell is 1:1:0.3; the mass ratio of polyvinyl pyrrolidone, polycaprolactone, asiaticoside and silver nanoparticles in the inner core is 1:1.5:0.33:0.13;

[0131] The preparation method of the fiber dressing is as follows:

[0132] (1) mixing polyvinyl pyrrolidone, polycaprolactone, curcumin, DMF and anhydrous ethanol to obtain a shell spinning solution, wherein the mass concentration of polyvinyl pyrrolidone is 1.7%, the mass concentration of polycaprolactone is 1.7%, the mass concentration of curcumin is 0.5%, the mass ratio of DMF to anhydrous ethanol is 9:1, and the mass ratio of polyvinyl pyrrolidone, polycaprolactone and curcumin in the shell spinning solution is 1:1:0.3;

[0133] (2) mixing polyvinyl pyrrolidone, polycaprolactone, asiaticoside, silver nitrate, DMF and tetrahydrofuran to obtain a core spinning solution, wherein the mass concentration of polyvinyl pyrrolidone is 1.5%, the mass concentration of polycaprolactone is 2.25%, the mass concentration of asiaticoside is 0.5%, the mass concentration of silver nitrate is 0.3%, the mass ratio of DMF to tetrahydrofuran is 1.05:1, and the mass ratio of polyvinyl pyrrolidone, polycaprolactone, asiaticoside and silver nitrate in the core spinning solution is 1:1.5:0.33:0.2;

[0134] (3) The ambient temperature was controlled at 35°C, and the ambient humidity was controlled at 25RH%. A hydrophobic spray was sprayed on the receiving device of the electrospinning machine. The coaxial electrospinning pillow was placed 21 cm away from the receiving end. The flow rate of the outer shell spinning solution was 1.2 mL / h, and the flow rate of the inner core spinning solution was 0.6 mL / h (the flow rate ratio of the outer shell spinning solution to the inner core spinning solution was 2:1). The voltage was increased by 18 kV to form a Taylor cone at the needle tip. The electrospinning was performed for 3 hours. The fiber membrane was removed from the receiving end and dried in an oven at 45°C for 24 hours to obtain a fiber dressing.

[0135] Embodiment 15

[0136] A fiber dressing for promoting wound healing, comprising micro-nano fibers with a core-shell structure, wherein the outer shell of the fiber is composed of polyvinyl pyrrolidone (average molecular weight 360,000 Da), polycaprolactone (average molecular weight 18,000 Da) and curcumin; the inner core of the fiber is composed of polyvinyl pyrrolidone (average molecular weight 360,000 Da), polycaprolactone (average molecular weight 18,000 Da), asiaticoside and silver nanoparticles; the mass ratio of polyvinyl pyrrolidone, polycaprolactone and curcumin in the outer shell is 1:1:0.3; the mass ratio of polyvinyl pyrrolidone, polycaprolactone, asiaticoside and silver nanoparticles in the inner core is 1:1:0.33:0.13;

[0137] The preparation method of the fiber dressing is as follows:

[0138] (1) mixing polyvinyl pyrrolidone, polycaprolactone, curcumin, DMF and anhydrous ethanol to obtain a shell spinning solution, wherein the mass concentration of polyvinyl pyrrolidone is 1.7%, the mass concentration of polycaprolactone is 1.7%, the mass concentration of curcumin is 0.5%, the mass ratio of DMF to anhydrous ethanol is 9:1, and the mass ratio of polyvinyl pyrrolidone, polycaprolactone and curcumin in the shell spinning solution is 1:1:0.3;

[0139] (2) mixing polyvinyl pyrrolidone, polycaprolactone, asiaticoside, silver nitrate, DMF and tetrahydrofuran to obtain a core spinning solution, wherein the mass concentration of polyvinyl pyrrolidone is 1.5%, the mass concentration of polycaprolactone is 1.5%, the mass concentration of asiaticoside is 0.5%, the mass concentration of silver nitrate is 0.3%, the mass ratio of DMF to tetrahydrofuran is 1.05:1, and the mass ratio of polyvinyl pyrrolidone, polycaprolactone, asiaticoside and silver nitrate in the core spinning solution is 1:1:0.33:0.2;

[0140] (3) The ambient temperature was controlled at 35°C, and the ambient humidity was controlled at 25RH%. A hydrophobic spray was sprayed on the receiving device of the electrospinning machine. The coaxial electrospinning pillow was placed 21 cm away from the receiving end. The flow rate of the outer shell spinning solution was 1.2 mL / h, and the flow rate of the inner core spinning solution was 0.6 mL / h (the flow rate ratio of the outer shell spinning solution to the inner core spinning solution was 2:1). The voltage was increased by 18 kV to form a Taylor cone at the needle tip. The electrospinning was performed for 3 hours. The fiber membrane was removed from the receiving end and dried in an oven at 45°C for 24 hours to obtain a fiber dressing.

[0141] Comparative Example 1

[0142] The curcumin, asiatica glycoside and silver nanoparticles in Example 3 were omitted, and other parameters were the same as those in Example 3, to obtain a blank fiber dressing, which was recorded as No-loaded.

[0143] Comparative Example 2

[0144] The asiaticaside and silver nanoparticles in the core of Example 3 were omitted, and other parameters were the same as those in Example 3, thereby obtaining a fiber dressing containing curcumin only in the shell, which was recorded as CUR-loaded.

[0145] Comparative Example 3

[0146] The curcumin in the shell and the silver nanoparticles in the core of Example 3 were omitted, and other parameters were the same as those of Example 3, thereby obtaining a fiber dressing containing only asiatica glycoside in the core, which was recorded as AS-loaded.

[0147] Comparative Example 4

[0148] The curcumin in the shell and the asiaticoside in the core of Example 3 were omitted, and other parameters were the same as those of Example 3, thereby obtaining a fiber dressing in which only the core contained silver nanoparticles, which was recorded as Ag-loaded.

[0149] Test Example 1: Appearance and morphology test

[0150] The macroscopic optical image, microscopic SEM image and SEM image of a single broken fiber of the fiber dressing in Example 3 are shown in FIG. Figure 1 As shown. Figure 1 It can be seen that the fiber dressing in Example 3 is composed of micro-nano fibers, and the micro-nano fibers have a core-shell structure. The presence of curcumin makes the fiber dressing present a yellow appearance.

[0151] Test Example 2: Biocompatibility Test

[0152] The fiber dressings in Example 3 and Comparative Examples 1 to 4 and a 20% mass concentration of dimethyl sulfoxide solution were co-cultured with high-glucose aged human umbilical vein endothelial cells (HUVECs), human fibroblasts (HDFs), and mouse macrophages (RAW264.7s), respectively, and CCK8 cytotoxicity assay was performed. The results are as follows: Figures 2 to 4 As shown, Figure 2 The figure is a graph showing the cytotoxicity of the fiber dressings in Example 3 and Comparative Examples 1 to 4 to HUVECs; Figure 3 The figure is a graph showing the cytotoxicity of the fiber dressings in Example 3 and Comparative Examples 1 to 4 to HDFs; Figure 4 The figures are the cytotoxicity graphs of the fiber dressings in Example 3 and Comparative Examples 1 to 4 to RAW264.7s at different culture days, wherein A is the cytotoxicity graph of the fiber dressings in Example 3 and Comparative Examples 1 to 4 to RAW264.7s on the first culture day (Day 1); B is the cytotoxicity graph of the fiber dressings in Example 3 and Comparative Examples 1 to 4 to RAW264.7s on the third culture day (Day 3). Figures 2-3 From left to right in the figure are the control group, comparative example 1, comparative example 2, comparative example 3, comparative example 4, embodiment 3 and 20% DMSO group.

[0153] from Figures 2 to 4 It can be seen that the fiber dressing provided by the present invention will not cause the death of HUVECs and HDFs in a high-sugar microenvironment after being co-cultured with them for 24 hours. There is no obvious cytotoxicity after being co-cultured with RAW264.7s for 24 hours. However, when the fiber dressing is co-cultured with RAW264.7s for 72 hours, the activity of RAW264.7s is significantly reduced. These results show that the fiber dressing provided by the present invention has good biocompatibility for skin repair-related cells. The polarizing drugs released in the first stage do not affect the activity of macrophages, while the drugs released in the second stage will significantly reduce the activity of macrophages, achieving further anti-inflammatory effects.

[0154] Test Example 3: Macrophage Polarization Experiment

[0155] First, M1 macrophages were obtained by lipopolysaccharide (LPS) treatment. The construction method was as follows: macrophages (RAW264.7) were planted in a high-glucose medium containing 100 ng / mL LPS, 25 mM glucose and 10% fetal bovine serum and cultured for 24 hours. Secondly, a RAW264.7 polarization experiment was carried out. RAW264.7 was planted in a 24-well plate and divided into 5 groups. Equal amounts of the fiber dressings of Example 3 and Comparative Examples 1 to 4 were added to the RAW264.7 culture medium, with 3 replicate wells in each group. The expression of CD86 and CD206 molecules was detected by cell immunofluorescence. CD86 (green) represents M1 macrophages, and CD206 (red) represents M2 macrophages. The results are as follows Figure 5 shown.

[0156] from Figure 5 It can be seen that only Comparative Example 2 and Example 3 have a significant effect of promoting the polarization of M1 macrophages to M2 macrophages, that is, the number of red cells is significantly increased and the number of green cells is significantly reduced. This is because the polarization-promoting drugs loaded in the outer phase of the fiber dressing are dissolved in the cell culture medium, inducing the polarization of M1 macrophages to M2 macrophages. It can be seen from Comparative Example 3 and Example 3 that the number of RAW264.7 is slightly reduced, which is due to the effect of the loaded drug that induces macrophage death.

[0157] Test Example 4: Inhibition Zone Experiment

[0158] Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) were respectively 1*10 7 CFU / mL was coated on an agar plate, and the fiber dressings (sterile, 10 mm in diameter, 500 μm in thickness) of Example 3 and Comparative Examples 1 to 4 were carefully attached to the agar plate evenly coated with bacteria, cultured at 37 degrees for 24 hours, and photographed to observe the diameter of the inhibition zone (optical image) and made quantitative statistics (bar graph). The results are shown in Figure 6 As shown, Figure 6 A is the diameter of the antibacterial zone of the fiber dressings of Example 3 and Comparative Examples 1 to 4 against E. coli (optical image); B is a quantitative statistical graph of the antibacterial performance of the fiber dressings of Example 3 and Comparative Examples 1 to 4 against E. coli; C is the diameter of the antibacterial zone of the fiber dressings of Example 3 and Comparative Examples 1 to 4 against S. aureus (optical image); D is a quantitative statistical graph of the antibacterial performance of the fiber dressings of Example 3 and Comparative Examples 1 to 4 against S. aureus. Figure 6 It can be seen that both Comparative Example 4 and Example 3 have obvious antibacterial activity against E. coli, and the diameter of the inhibition zone is significantly larger than that of the other groups; similarly, they also have obvious antibacterial activity against S. aureus, and the diameter of the inhibition zone is significantly larger than that of the other groups.

[0159] Test Example 5: In vitro non-stimulation on-demand controllable adhesion test

[0160] A clean glass slide (3 cm long, 1 cm wide) was attached to the tensile testing machine test bench with double-sided tape, and ultrapure water of different volumes was evenly distributed on the glass slide. The fiber membrane in Example 3 (5 cm long, 1 cm wide, and 500 μm thick) was pressed on the water-coated glass substrate with a pre-pressure of 5 N. The adhesion strength of the fiber dressing in Example 3 on surfaces with different water contents was then investigated using a 90° peeling method. The results are shown in FIG. Figure 7 shown.

[0161] from Figure 7 It can be seen that when the substrate water content is 15uL, the fiber dressing has a higher peel strength, about 1.5N / cm. As the substrate water content increases, the peel strength of the fiber dressing gradually decreases, indicating that the fiber dressing has a non-irritating, on-demand controllable adhesion effect.

[0162] Test Example 6: In vivo non-stimulation on-demand controllable adhesion experiment

[0163] C57 mice were anesthetized with 1wt% sodium pentobarbital, and full-thickness skin defects with a diameter of 10 mm were cut on the back of the mice using ophthalmic scissors. The fiber membrane in Example 3 (5 cm long, 4 cm wide, and 500 μm thick) was taken and its middle part was attached to the wound surface. After standing for 30 seconds, the fiber membrane in Example 3 was gradually lifted up, and no other fixation measures were taken on the mice. The height of the mice being lifted up was observed, and then a large amount of physiological saline was dripped on the wound surface. The peeling process of the fiber dressing was observed. The results are shown in FIG. Figure 8 shown.

[0164] from Figure 8 It can be seen that dressings can be easily changed by spraying normal saline on the wound surface without damaging the wound surface and surrounding tissues, reducing secondary damage during dressing changes.

[0165] Test Example 7: Effect of promoting the healing of full-thickness skin defect wounds in diabetic mice

[0166] Thirty 7-week-old female diabetic mice were randomly divided into five groups. After being anesthetized with 3% sodium pentobarbital, two skin full-thickness defect wounds with a diameter of 10 mm were constructed on the back of the mice. Then, 100 μL of 1×10 7CFU / mL of Staphylococcus aureus liquid was used to prepare an infectious diabetic wound model, and then the fiber membranes of Example 3 and Comparative Examples 1 to 4 were covered on the wound surface respectively, and the mice were raised in the same environment. The wound surface was photographed on the 0th, 3rd, 7th, 10th and 14th days (optical images), and the wound healing speed was counted (quantitative images). On the 3rd and 7th days after the injury of the mice, the wound tissue was taken and ground to obtain tissue homogenate, and the number of bacteria present in the wound surface was analyzed by agarose plating method (optical images). The results are shown in FIG. Fig. 9 shown.

[0167] from Fig. 9 It can be seen that the wound healing rate of the infectious diabetic mice using Example 3 was the fastest. 14 days after the injury, the wound was basically closed, while the wound healing rate of the other groups of control groups was slower, and there were obvious unclosed areas on the wound after 14 days. This shows that Example 3 has a significant effect in promoting the healing of diabetic wounds. At the same time, it was found that the number of bacteria in the wound using Example 3 was the least 3 days after the injury, and the bacteria almost disappeared 7 days after the injury. However, there were still more bacteria in the other control groups. This shows that Example 3 has excellent antibacterial activity in vivo.

[0168] In summary, the fiber dressing provided by the present invention has excellent biocompatibility, controllable adhesion, antibacterial properties, multi-stage immunoregulatory properties, and excellent wound healing effects.

[0169] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A fiber dressing for promoting wound healing, comprising micro-nano fibers with a core-shell structure; the outer shell of the fiber comprises a first hydrophilic polymer, a first hydrophobic polymer and a first drug; the inner core of the fiber comprises a second hydrophilic polymer, a second hydrophobic polymer, a second drug and a third drug; the first drug comprises one or more of curcumin, naproxen, paeoniflorin, gallic acid, green tea extract, resveratrol, neurotensin, freeze-dried amniotic membrane-derived conditioned medium and miR-2235p mimics; the second drug comprises one or more of asiatica glycoside, quercetin, Fe3O4 nanoparticles, hemin, polyrotaxane containing methylated β-cyclodextrin, sorafenib, cyclosporine and Erastin; the third drug comprises one or more of silver nanoparticles, copper nanoparticles, antibacterial polypeptides and polyionic liquid antibacterial agents.

2. The fiber dressing according to claim 1, characterized in that: The mass ratio of the first hydrophilic polymer, the first hydrophobic polymer and the first drug in the shell is (1-10):1:(0.1-0.5).

3. The fiber dressing according to claim 1, characterized in that: The mass ratio of the second hydrophilic polymer, the second hydrophobic polymer, the second drug and the third drug in the inner core is 1:(1-10):(0.1-0.5):(0.1-0.2).

4. The fiber dressing according to claim 1, characterized in that: The first hydrophilic polymer and the second hydrophilic polymer independently include one or more of polyvinyl pyrrolidone, gelatin, sodium alginate, carboxymethyl chitosan, polyvinyl alcohol, polyacrylic acid, recombinant spider silk protein, silk protein, polyethylene glycol, polyethylene oxide, tannic acid adhesive, dextran and pectin.

5. The fiber dressing according to claim 1, characterized in that: The first hydrophobic polymer and the second hydrophobic polymer independently include one or more polymers selected from the group consisting of polycaprolactone, polyurethane, polylactic acid, polylactic acid-co-glycolic acid, cellulose acetate, polydimethylsiloxane, polymethacrylate, polyvinylidene fluoride, polyvinyl acetate, polyester, thermoplastic polyurethane elastomer, ethylene-vinyl acetate polymer, polyamide, polyimide and polylactic acid-co-glycolic acid and their derivatives.

6. A method for preparing the fiber dressing for promoting wound healing according to any one of claims 1 to 5, comprising a coaxial electrospinning method, a near-field direct writing method, a microfluidic spinning method or an immersion pulling method.

7. Use of the fiber dressing for promoting wound healing according to any one of claims 1 to 5 or the fiber dressing for promoting wound healing prepared by the preparation method according to claim 6 in preparing wound dressings.

Citation Information

Patent Citations

  • Traditional Chinese medicine asiaticoside carrying core / shell structure nanometer fiber film preparation method and wound dressing use

    CN106075539A

  • Hydrophilic fibrous membrane with sustained-release medicine as well as preparation method and application of hydrophilic fibrous membrane

    CN115350316A

  • Application of composite nanofiber membrane in preparation of medicine for promoting healing of diabetic wound

    CN116270555A

Cited By

  • Wound healing promoting medical dressing and preparation method thereof

    CN120458830A

  • Percolate responsive self-shedding core-shell microgel powder for burn and scald wounds and preparation method of percolate responsive self-shedding core-shell microgel powder

    CN121714756A

  • Biological hemostatic dressing, preparation method and application

    CN122321198A